With God on Our Side The Struggle for Workers' Rights in a Catholic Hospital - Reich, Adam D. (Cornell University Press, 2012)
When unions undertake labor organizing campaigns, they often do so from strong moral positions, contrasting workers' rights to decent pay or better working conditions with the more venal financial motives of management. But how does labor confront management when management itself has moral legitimacy? In With God on Our Side, Adam D. Reich tells the story of a five-year campaign to unionize Santa Rosa Memorial Hospital, a Catholic hospital in California. Based on his own work as a volunteer organizer with the Service Employees International Union (SEIU), Reich explores how both union leaders and hospital leaders sought to show they were upholding the Catholic "mission" of the hospital against a market represented by the other. Ultimately, workers and union leaders were able to reinterpret Catholic values in ways that supported their efforts to organize.More generally, Reich argues that unions must weave together economic and cultural power in order to ensure their continued relevancy in the postindustrial world. In addition to advocating for workers' economic interests, unions must engage with workers' emotional investments in their work, must contend with the kind of moral authority that Santa Rosa Hospital leaders exerted to dissuade workers from organizing, and must connect labor's project to broader conceptions of the public good.When unions undertake labor organizing campaigns, they often do so from strong moral positions, contrasting workers' rights to decent pay or better working conditions with the more venal financial motives of management. But how does labor confront management when management itself has moral legitimacy? In With God on Our Side, Adam D. Reich tells the story of a five-year campaign to unionize Santa Rosa Memorial Hospital, a Catholic hospital in California. Based on his own work as a volunteer organizer with the Service Employees International Union (SEIU), Reich explores how both union leaders and hospital leaders sought to show they were upholding the Catholic "mission" of the hospital against a market represented by the other. Ultimately, workers and union leaders were able to reinterpret Catholic values in ways that supported their efforts to organize.More generally, Reich argues that unions must weave together economic and cultural power in order to ensure their continued relevancy in the postindustrial world. In addition to advocating for workers' economic interests, unions must engage with workers' emotional investments in their work, must contend with the kind of moral authority that Santa Rosa Hospital leaders exerted to dissuade workers from organizing, and must connect labor's project to broader conceptions of the public good.